La imputabilidad de las personas mayores de 16 años y menores de 18 años, por hechos delictivos - Castillo Delgado, Vladimir Alexander (2015)
The present work explains the juridical and social foundations in order that the minor teenagers of 18 and major of 16 years they should be fullly attributable under the rules that the ordinary criminal law establishes to the moment of the cometimiento of serious, such crimes as murder, theft and sexual crimes.. The main points of this writing is not to modify or eliminate the special system of treatment seat up for minors, but to change the legal age limit that would transfer them to the ordinary penal system for adults. That is why the investigation was initiated in the knowledge of the problem, its scope and standards that can be applied in their study, the theoretical framework deepens theoretical aspects that substantiate scientifically the subject, for it is an analysis of national and International Instruments which are considered applicable, and its true value within our legal system, that the minor teenagers of 18 and major of 16 years they are fullly attributable precisely to assure the citizens the life, the conviviality, the work, the justice, the equality, the knowledge, the freedom and the peace, inside a juridical, democratic and participative frame that should guarantee a political, economic and social just order. Finally, refers to the purposeful development of the framework, where the researcher submits a proposal in an effort to provide a legal basis of the problem in question, and especially the Penal Code to incorporate the that the minor teenagers of 18 and major of 16 years theyare fullyyears for crimes against life as part of the solutions proposed at the beginning of the investigation